PERBANDINGAN PENERAPAN METODE DEMONSTRASI DAN METODE CERAMAH TERHADAP HASIL BELAJAR DRIBBLE BOLA BASKET (STUDI PADA SISWA KELAS V SDK STELLA MARIS SURABAYA) - MANJELA ETO, TOMI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The Learning of basketball game is one of sport which included in the school curriculum, therefore in order cultivating students' interest in learning basketball game required varied teaching model and interesting for the students in order to create a sense of fun and joy so that student interest in basketball game learning especially to mastery dribble techniques will increase. Several learning methods of physical education that can be applied such as demonstration method and lecture method. The purpose of this study was to determine: (1) The difference between learning outcomes of basketball dribbling while using demonstration method and lecture method in grade V Stella Maris Catholic Elementary School Surabaya. (2) How large the differences of learning outcomes of basketball dribbling while using demonstration method and lecture method. The objectives of this research are  the students of grade V Stella Maris Catholic Elementary Schooll Surabaya Academic Year 2011/2012. The conclusion: (1) There is significant difference between students in group I (Demonstration Method) and group II (Lecture Method) in dribbling basketball learning. The test result of average difference between groups showed that the tvalue 4.505 greater than the value of ttable 2.045. (2) The demonstration learning method deliver improved students’ learning outcomes in dribbling basketball by 5.90% while the lecture method turned out to provide an increase of 2.28%. It can be argued that learning by demonstration method gives a better effect than the lecture method to improving students’ learning outcomes in dribbling basketball at grade V Stella Maris Catholic Elementary School Surabaya.     Keywords: Learning Method, Demonstration, Lecture, Dribbling, Basketball.